Heavy metal elimination from industrial wastewater using natural substrate on pitcher irrigation - Negar Nourmahnad; Kamran Asgari; Najmeh Samadi (International Journal of Recycling of Organic Waste in Agriculture)
Combination of pitcher irrigation with drip irrigation system could be resulted in prolonging the secondary treatment period, as it could be an efficient system in which municipal and industrial wastewater can be treated and heavy metals can be reduced. For this purpose, an experiment was conducted with three treatments [clay pitcher included natural zeolite Clinoptilolite (NZ), perlite (P) and vermiculite (V)] which filled half of the volume of a clay pitcher with five replications for each treatments. Beside each tree, one pitcher was placed at 50 cm depth. The soil of each hole was initially sampled, sealed, and transported to the laboratory. The pitchers were irrigated with treated industrial wastewater (from steel factory) 60 times (1500 cc per each irrigation event) over a period of six months. At the end of experiment period, the pitchers were removed and samples were taken from the substrate inside each pitcher and from the soil near the walls and bottoms of the holes. The sealed samples were transported to the laboratory for analyzing heavy metals (Fe, Cd, Cr, Cu, Pb, Mn, and Zn) using an atomic absorption spectrophotometer. The results showed that the used substrates in this experiment have high ability to absorb some heavy metals, especially Pb and Zn which concentration were increased in final value 75 and 80 times compared with initial values, respectively. However, an increase of these two elements in the soil (Zn = 26 and Pb = 71 ppm) nearby the pitcher indicate that the used substrates have limitations in absorption capacity for the heavy metals in high concentration of them in the wastewater. As this is related to their surface area, application of a nano form of the substrates such as nano zeolite might remarkably increase their cation exchange capacity and surface area.